2019
DOI: 10.3390/min9100571
|View full text |Cite
|
Sign up to set email alerts
|

Sintering Optimisation and Recovery of Aluminum and Sodium from Greek Bauxite Residue

Abstract: Bauxite residue is treated for the recovery of aluminum and sodium by sintering with the addition of soda, metallurgical coke and other reagents such as CaO, MgO and BaO. A thorough thermodynamic analysis using Factsage 7.0™ software was completed together with XRD mineralogy of sinters with different fluxes and reagents additions. Through both thermodynamic interpretation and mineralogical confirmations, it was observed that the type of desilication product in bauxite residue influences the total aluminum rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A behavior of the Reactions (4) and ( 5) depends on chemical composition of the raw materials. In the system with red mud sample B (Figure 4) the Reactions (4) and ( 5 [59,60] that can complicate following extraction of aluminum from the tailings. In the system with red mud sample U (Figure 5) high content of calcium inhibits the Reaction (5) by calcium silicate 3CaO•2SiO 2 generation.…”
Section: Thermodynamic Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A behavior of the Reactions (4) and ( 5) depends on chemical composition of the raw materials. In the system with red mud sample B (Figure 4) the Reactions (4) and ( 5 [59,60] that can complicate following extraction of aluminum from the tailings. In the system with red mud sample U (Figure 5) high content of calcium inhibits the Reaction (5) by calcium silicate 3CaO•2SiO 2 generation.…”
Section: Thermodynamic Calculationsmentioning
confidence: 99%
“…It is well-known that addition of CaO during sodium sintering of red mud (sinter leach process) leads to the formation of Ca 2 SiO 4 phase, which improves subsequent aluminum recovery by leaching [58][59][60]. On the other hand, CaO addition can decrease iron content in the magnetic concentrates obtained after solid phase reduction at low temperatures [61,62].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have been performed to recover major components of the BR. 10,53 Our results highlight the importance of the nature of lixiviants for designing an integrated process for metal recovery from the BR. It has been shown that the selectivity of the SILP is greatly affected by the solvent (water or ethanol).…”
Section: ■ Results and Discussionmentioning
confidence: 73%
“…Still, aluminum can be recovered beforehand from the BR, for instance, by sintering processes. 53 , 54 Several factors can have an impact on the selectivity of the sorption process from the mixture of aqueous–organic solvents, apart from the solvation and the formation of negatively charged complexes. They include the strength of the cation–organic solvent interactions, hydrogen bonding, the dielectric constant of the medium, and the standard molar free energies of transfer of single cations between different media.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Wai et al [43] investigated the effect of CaO, MgO, and BaO addition on the aluminum and sodium recovery from red mud after sintering with Na 2 CO 3 . The mixtures of red mud, 25% of soda, and various additives in the amount of 20% were sintered at 900 • C for 2 h and then leached in 0.1 M NaOH solution.…”
Section: Sintering Processmentioning
confidence: 99%